Single-Case Writing Interventions for Students with Disorders of Intellectual Development: A Systematic Review and Meta-Analysis - Randi Karine Bakken; Kari-Anne Bottegaard Næss; Veerle Garrels; Åste Mjelve Hagen (MDPI AG, 2022)
Students with disorders of intellectual development (ID) often experience writing difficulties, and effective interventions are highly needed. This systematic review and meta-analysis of single-case experimental design (SCED) studies summarize the effects of writing interventions for students with disorders of ID aged 4-19 years. We conducted a systematic search of seven databases, ancestral and forward searches of relevant sources, and contacted well-known authors in the field. Fifteen and 10 studies were included in the systematic review and meta-analyses, respectively. The overall results indicate that the participants improved their writing skills, with a large between-case standardized mean difference (BC-SMD) effect on the number of words and sentences written (BC-SMD = 1.22) and on the quality of paragraph and story writing (BC-SMD = 1.39). Students with disorders of ID can benefit from writing interventions, and the study results may provide practitioners with important insight into promising writing instructions and materials. There is a need for high-quality research targeting encoding (i.e., transforming sound into letters) skills for early school-age students with disorders of ID.